The Role of Knowledge Management in Adopting Industry 4 Technology: The Mediating Role of Market Orientation - Khedr, Wessam; Gohar, Nermin (The Arab Journal of Administration, 2023)
Industry 4.0 is a concept that refers to the widespread adoption of modern techniques such as big data analytics, the Internet of Things (IoT), and artificial intelligence (AI). It can be adopted using different knowledge management (KM) activities. Thus, this research seeks to explore the impacts of KM activities on Industry 4.0 adoption through the mediating functions of market orientation. Precisely, the paper investigated the effects of some KM activities, namely: Knowledge Creation, Knowledge Acquisition, Knowledge Sharing, Knowledge Storage, Knowledge Dissemination, and Knowledge Application on Industry 4.0 adoption in Egyptian manufacturing and service companies. To achieve the aim of this study, a questionnaire was employed to investigate the assigned relationships in the manufacturing and service sectors in the Egyptian context. Data was collected from 666 respondents and analyzed using SEM analysis. Results revealed that all studied KM activities (Creation of Knowledge, Acquisition of Knowledge, Sharing of Knowledge, Storage of Knowledge, and Knowledge Dissemination) were found to have positive significant effects on Industry 4.0 adoption and market orientation. Additionally, market orientation has a significant influence on Industry 4.0 adoption and performs a limited mediation role in the relationship between KM activities and Industry 4.0 adoption. Further statistical analysis confirmed that the level of KM activities or the degree of technology 4 adoption; and market orientation, would differ according to organization size, maturation stage, sector and organization type. Practical implication and theoretical contribution for future research is provided.